EFEKTIVITAS PENGGUNAAN KARBON AKTIF DAN KARANG JAHE SEBAGAI FILTRASI UNTUK MENURUNKAN KADAR AMONIAK LIMBAH CAIR RUMAH SAKIT SEMEN GRESIK - Asti Chairani Putri; Sulistyani Sulistyani; Mursid Rahardjo (Jurnal Kesehatan Masyarakat (Undip), 2017)
Semen Gresik Hospital produces liquid waste with ammonia levels that can cause water contamination. Based on preliminary study in May 2017, the amount of ammonia waste of Semen Gresik Hospital was 0,51 mg/L. This level still does not meet the quality standard of hospital waste ammonia at 0,1 mg/L. Therefore the need for further action in treating the polluted liquid waste hospital is filtration method with activated carbon and ginger coral. The purpose of this study is to determine the effectiveness of the use of activated carbon and ginger corals as filtration to reduce the level of ammonia liquid waste Semen Gresik Hospital. This type of research is a pretest-posttest with control group experimental design. This treatment uses a variety of 60 cm of active carbon media, 60 cm ginger coral and a combination of activated carbon and ginger corals each 30 cm. Anova One Way Test with 95% confidence degree indicates that there is a difference of average decrease of ammonia waste water content of hospital with various variation of media type. Post Hoc test results show that there are significant differences between variations of activated carbon medium with ginger coral, variation of activated carbon with combination of activated carbon and ginger reef, variation of activated carbon with control, ginger coral variation with control, and combination of activated carbon and ginger reef with control in reducing the level of wastewater ammonia (p≤0,05). Average ammonia efficiency after treatment with activated carbon is the highest ammoniac decrease that is 88,2% or can decrease ammonia level up to 0,134 mg / L.